Study on the interaction between diet, quercetin and intestinal microbiota (2020)
Flavonoids are secondary metabolites of plants which have anti-cancer, anti-inflammatory, and antioxidant properties. However, the intestinal microbiota can change the bioactivity and bioavailability of these compounds, which may trigger different levels of response to a treatment. In order to expand our understanding of the capacity of the gut microbiota to modify these therapeutic compounds, we explored the microbial degradation of quercetin, one the most abundant flavonoids in the human diet. First, we revealed that a non-quercetin degrader (Bacteroides thetaiotaomicron) can provide, via crossfeeding, substrates to a quercetin-degrader (Eubacterium ramulus) for the cometabolization of the flavonoid. Second, through a metataxonomic analysis of fecal communities exposed to the flavonoid, we detected two variants related to the quercetin degrader, Flavonifractor plautii, that presented a negative correlation in their relative abundances upon incubation with quercetin. Lastly, a bioinformatic analysis of the genome of the closest relatives of these variantsshowed that they are discordant for the catabolism of an important substrate in the gastrointestinal tract, ethanolamine, which it is formed from bacterial and intestinal cell membranes and is abundant even in the absence of dietary compounds due to the constant washing away of these cells in the intestinal mucus. Overall, these observations indicate that flavonoid-degrading bacteria can be differentially affected by dietary and host¿s substrates and interactions with different microbial species. Thus, the community structure and metabolic capacity of each individual¿s gut microbiota may impact the health-related effects of these compounds.